Stereotype Content at the Intersection of Gender and Sexual Orientation - Klysing, Amanda; Lindqvist, Anna; Björklund, Fredrik (Frontiers in Psychology, 2021)
According to the Stereotype Content Model, the content of stereotypes differs on two dimensions: communion and agency. Research shows that for stereotypes about the general gender categories of ‘“women’” and ‘“men’”, there is an ambivalent pattern of communion and agency where high levels on one dimension are associated with low levels on the other. For sexual minority stereotypes, a gender inversion has been found where homosexual women are seen as more similar to men in general than to women in general, whereas homosexual men are seen as more similar to women in general than to men in general. However, there is limited research on how stereotype content for general groups relate to stereotype content for subgroups with intersecting category memberships. This research addresses this gap by investigating stereotype content at the intersection of gender and sexual orientation, including stereotype content for general gender groups, heterosexual groups, homosexual groups, and bisexual groups. In Study 1, a community sample from Sweden (N=824) rated perceived communion and agency for women and men in general, as well as hetero-, homo- and bisexual women and men. In Study 2, a nationally representative Swedish sample (N=424) performed the same rating task, and in addition completed Single-Category IATs for warmth and competence. Results from both studies show that the stereotype content for the general categories ‘“women’” and “’men’” overlap with the stereotype content for heterosexual same-gender targets. Homosexual and bisexual groups were rated as more similar to their non-congruent gender category than same gender heterosexual categories were, but stereotype content for sexual minority groups did not overlap with either general gender categories, thus showing only incomplete gender inversion of stereotype content. Implicit associations between ‘women’ and ‘warmth’ were significantly stronger than associations between ‘men’ and ‘warmth’. There were no other significant relations between implicit associations to warmth/competence and gender or sexual orientation. Theoretical and methodological implications for future research into intersectional stereotype content are presented, including how the findings inform the co-dependent relationship between a binary gender structure and a heteronormative ideology.